2023
DOI: 10.1136/bmjopen-2022-061564
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to family planning use in the Eastern Democratic Republic of the Congo: an application of the theory of planned behaviour using a longitudinal survey

Abstract: ObjectiveIn the Democratic Republic of the Congo, there is a low adherence of the population to the use of family planning (FP) due to various social barriers. This study aimed to understand the drives from social barriers to the use of FP in women in the Kivu, a region particularly affected by poverty and many years of conflicts. A theory of planned behaviour (TPB) using a generalised structural equation modelling has been applied to understand the complex sociocultural drivers to the intention and the ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Furthermore, the perceptions of family and peer groups appeared to strongly in uence decisions regarding family size, with certain members advocating for birth spacing while others encouraged couples to "multiply and ll the earth". Subjective norms, such as the belief that "children are a gift from God" and the perception that contraceptives are sinful, as demonstrated by a study in Eastern Congo, are found to have a negative and signi cant association with the intention to use family planning [21]. Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size.…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 48%
“…Furthermore, the perceptions of family and peer groups appeared to strongly in uence decisions regarding family size, with certain members advocating for birth spacing while others encouraged couples to "multiply and ll the earth". Subjective norms, such as the belief that "children are a gift from God" and the perception that contraceptives are sinful, as demonstrated by a study in Eastern Congo, are found to have a negative and signi cant association with the intention to use family planning [21]. Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size.…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 48%
“… 8 However, misinformation and lack of information are key barriers to FP uptake in the DRC, 8 while FP education in that area has been shown to be significantly positively associated with intention to use FP. 10 …”
Section: Introductionmentioning
confidence: 99%
“…8 However, misinformation and lack of information are key barriers to FP uptake in the DRC, 8 while FP education in that area has been shown to be significantly positively associated with intention to use FP. 10 The USAID Integrated Health Program in the Democratic Republic of the Congo (USAID IHP) works closely with the Government of the DRC's Ministry of Public Health, Hygiene, and Prevention (MSPHP), along with other stakeholders, to strengthen their capacity in delivering high quality, integrated health services in several health areas, including FP. The USAID IHP is the largest USAID health project in the DRC.…”
Section: Introductionmentioning
confidence: 99%